Implementasi Peraturan Bupati Nomor 6 Tahun 2016 Tentang Standarisasi Usaha Pondok Wisata Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Badung Provinsi Bali - Komang Ayu Kusuma Wardani (Universitas Mahendradatta Denpasar, 2019)
Badung district as one of the regions applying local autonomy made a policy of tourismaccommodation stipulated in the Regent Regulation Number 6 Year 2016 on Standardization ofCottages Business.This regulation was a follow-up of building structuring supervision ofaccommodation service in Badung District, as a technical requirement for accommodation service witha narrow area of land by following the standard of cottages business.The objectives of this researchwere to determine how the implementation, implementation strategy and supporting factors are ofRegent Regulation Number 6 Year 2016 on the Standardization of Cottages Business. This was adescriptive qualitative research. In order to collect the data, the researchers conducted an observationand interview with information sources relating to the implementation of that regulation.The researchresult showed that the implementation of this research was not optimum yet, there was a violation ofthe implementation and the license. Badung tourism service as the executor seems like ignoring thatmatter since the government wants to have a local revenue increase accepted from the tax determinationfor business by 10%. The implementation strategy was conceptualized as a Tourism Village, but thecondition at field did not support. Supporting factors of this regulation implementation werecommunication and good cooperation among the executors, potential of spatial planningimplementation, and the potential to increase Badung local own-source revenue. While the inhibitingfactors were the target group behavior diversity and commitment degree as well as executors ‘ability.